Predicting Factors Affecting Dental Patient Compliance in Primary Health Care - Ahmed Eid Alatawi,; Naser Mohammad Naser Marzok,; Zaid Hlail Sulaiman Albalawi,; Majed Awdah Sulayman Alqarani,; Majed Abdulmohsen Alobaid,; Muteb Hussain Mohsen Alsarrani,; Hadeel Mustafa Alyamni,; Muruj Ibrahim algethami,; Waleed Masad Alhuthali,; Shuaa Jamal Abdulrahman Altwaijri,; Abdullah Ghothyman Mohammed Alhubaishi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The compliance of dentists with good hygiene practices was essential to minimize the transmission of infection, and the infection cycle has significantlyinterrupted the provision of oral health care to many individuals. Aim of study: aimed to examine, actors affecting dental patients’ compliance in primary dental health. Research design: descriptive cross-sectional research design was utilized. The present study was conducted on 300 dental patients visiting four privatedental offices in primary health care at Gaddah during the period June to august.Twenty-five of the participants indicated that they had visited a dentist for teeth cleaning in the past year when asked if they had complied with the recommendation. In the meanwhile, most stated that they intended to postpone prosthetic procedures (crown placements, implants, or dentures) out of concern for the spread of infection. The overwhelming majority of participants (59%) acknowledged the crucial role that dentists play in primary healthcare. "Has your fear of infection prevented you from attending your scheduled dental appointments?" 25% of respondents said they would be influenced if they knew the dentist had an infection, whereas 70% said they had not been impacted. Eighty-eight percent of interviewees said they would feel more secure if they knew their dentist was vaccinated. conclusion Based on patient views, we found that dentists had sufficient knowledge, attitudes, and practices regarding infection control methods. When performing dental work on patients, the great majority of dental professionals demonstrated a solid understanding of hand hygiene and adhered to all health precautions against cross-infection as directed by public health authorities.